Nicolas Standaert, Ad Dudink (eds). Forgive Us Our Sins. Confession in Late Ming and Early Qing China - Poškaitė, Loreta (Acta Orientalia Vilnensia, 2007)
Nicolas Standaert, Ad Dudink (eds). Forgive Us Our Sins. Confession in Late Ming and Early Qing China, Monumenta Serica Monograph Series LV, Sankt Augustin: Institut Monumenta Serica, 2006, pp. 268. IS BN-10: 3-8050-0540-1, ISSN 0179-261X